IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI KOTA PALU - Talib, Talib (Katalogis, 2014)
Cleannes is closely related to garbage and this is a crucial issue in urban environment facedby the goverment along with growing population and development. The purpose of this research was to how is garbage management policy implemented in Palu and what are the inhibiting and supporting factors in the management. This research used a policy implementation model by Donald Van Metter and Charls Van Horn in the aspects of standard and target, resources, organisational characteristics, and executor’s attitudes. This used a qualitative research by using 9 informants, taken purposively. The techniques of data analysis were observation, interview, and documentation. The techniques of data analysis were through editing data, categorising, interpreting, and drawing conclusion. The research shows that the policy on garbage management in Palu has not been implemented well due to some inhibiting factors: 1) there was no expert to support the policy, 2) operational cost as well as facility and infrastructure were limited and this caused huge garbage piled up in the spot, 3) the community’s participation was low. The supporting factors were the City Regulation No. 12, 2005 regarding city cleanness management, the Decree of Palu Mayor No 17, 2007 regarding garbage management to administrative village within Palu City and the support from the House of City Representatives and other stakeholders in order to promote clean and green city.